2019
DOI: 10.1108/jepp-03-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Crypto-friendliness: understanding blockchain public policy

Abstract: Purpose The purpose of this paper is to conceptualise the chief aspects of policy interest in blockchain technology. Design/methodology/approach The paper outlines policymaking processes in the context of innovation and technological change, assesses generic variations in policy treatment towards blockchain, and identifies manifestations of policy entrepreneurship using national case studies of blockchain policies. Findings Favourable policy dispositions towards blockchain technology are interpreted as pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Novak's research found beneficial policy inclination regarding blockchain technology is expounded as political efforts to evolve local, blockchain-enabled economies [58]. Policy makers in countries/regions that oppose blockchain-related activity have imposed prohibitions or strict restrictions on developers and users participating in blockchain activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novak's research found beneficial policy inclination regarding blockchain technology is expounded as political efforts to evolve local, blockchain-enabled economies [58]. Policy makers in countries/regions that oppose blockchain-related activity have imposed prohibitions or strict restrictions on developers and users participating in blockchain activities.…”
Section: Resultsmentioning
confidence: 99%
“…Mei and Liu [5] introduced the technical principles of blockchain, discussed its industry situations and existing problems, and proposed related policy suggestions for government, industry, and academic institutions. Novak [34] [37] pointed out that the effective supervision of financial blockchain technology is a issue which has to be resolved earnestly and propose risk prevention and regulatory policy recommendations. Truby [38] explored the regulatory, legal and policy related to blockchain technology and digital currencies for sustainable environmental development.…”
Section: Development Of Blockchain Industrial Policiesmentioning
confidence: 99%
“…The conditions of the external environment affect the adoption of BT and the entry and success of the BT-enabled firms. Countries that exhibit a more welcoming policy stance are more likely to attract entrepreneurs and investors in the cryptoeconomic blockchain space (Novak, 2019). Allen (2019) also suggests that the BT policy within early-stage entrepreneurship should focus on how existing policies inhibit the process of an emergent entrepreneurial organisation.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Mei and Liu introduced the technical principles of blockchain, discussed its industry applications and existing problems and proposed related policy suggestions for government, industry and academic institutions [5]. Novak built a blockchain "crypto-friendliness" model which can evaluate policy accommodation [30].…”
Section: Development Of Blockchain Industrial Policiesmentioning
confidence: 99%